Validation of the French version of the classroom assessment scoring system infant and toddler in Quebec - Lise Lemay; Paul Hayotte; Julie Lemire; Caroline Bouchard; Lorie-Marlène Brault-Foisy; Nathalie Bigras; Gilles Cantin (Institute of Advanced Engineering and Science, 2024)
The objective of this study is to validate the French version of the Classroom Assessment Scoring System (CLASS) infant and toddler, as employed to assess the quality of interactions in groups of children under 3 years old, in childcare centers in Quebec where French is the official language. Indeed, when using a different language version of a standard-based tool outside its original context, an important step is to verify that it remains reliable and valid for measuring the research construct. This validation study was conducted in Montreal area (Quebec, Canada). The subjects were 154 classrooms (46 infant, 108 toddler) located within a representative sample of 68 childcare centers. Live classroom observations were conducted in the fall 2018 with the CLASS and other measures of process quality. Results replicate the factor structures of the original versions of the CLASS tool and provide evidence for the good reliability (inter-rater reliability, internal consistency) and validity (criterion and construct) of the French versions. The discussion highlights cross-cultural differences in the classrooms, childcare centers, and regulations that could explain some differences obtained in this research and, therefore, needs to be considered when using the CLASS in French to have a reliable and valid tool to measure the quality of interactions.